Answer:
The solution is: (1,-3)
Explanation:
Given equations are:
x-y=4 Eqn 1
4x+y = 1 Eqn 2
Substitution involves finding value of a variable from one equation and putting in other equation
From equation 1
x = y + 4
Putting in equation 2
![4(y+4) + y = 1\\4y+16+y = 1\\5y = 1-16\\5y = -15\\(5y)/(5) = (-15)/(5)\\y = -3](https://img.qammunity.org/2022/formulas/mathematics/high-school/5g30e9ybzibwkr8gyfqh2ecnh8wptzjrvb.png)
Putting y = -3 in equation 1
![x- (-3) = 4\\x + 3 = 4\\x = 4-3\\x = 1](https://img.qammunity.org/2022/formulas/mathematics/high-school/7bk10eouok0ui2hb1q22axwz9iksm06sav.png)
Hence,
The solution is: (1,-3)